2016
DOI: 10.1016/j.freeradbiomed.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

9-Norbornyl-6-chloropurine (NCP) induces cell death through GSH depletion-associated ER stress and mitochondrial dysfunction

Abstract: quinone oxidoreductase (NQO-1) and glutamate cysteine ligase modifier subunit (GCLm), thus explaining the fast restoration of GSH pool and ROS decrease. Importantly, we confirmed that the cell death-inducing properties of the compounds were co-dependent on their ability to diminish cellular GSH level by analyzing the relationships between the GSH-depleting potency and cytotoxicity in a series of other norbornylpurine analogs. Altogether, the results demonstrated that in CCRF-CEM cells NCP triggered apoptosis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Elevated ROS levels have been reported to induce apoptosis by a series of downstream pathways including ER stress and mitochondrial dysfunction 27 . We determined whether increased ROS levels by Celastrol induce ER stress in gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated ROS levels have been reported to induce apoptosis by a series of downstream pathways including ER stress and mitochondrial dysfunction 27 . We determined whether increased ROS levels by Celastrol induce ER stress in gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that quercetin delivered in the form of nanoparticles induces ROS production and p53 loss, arrests the cell cycle in the sub-G phase, and induces apoptosis by mitochondrial pathways in HepG2 cells [ 15 ]. Despite the various mechanisms of quercetin in eliminating tumor cells and its numerous effects, several studies have reported that it does not harm normal cells [ 16 , 17 ]. Nevertheless, contradicting reports exist regarding the exact mechanism of action of quercetin.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, ROS accumulation and redox status perturbation disrupt protein folding in the ER, causing ER stress (Plackova et al, 2016). Therefore, we attempted to understand whether PL induced ROS-dependent apoptosis was associated with ER stress.…”
Section: Resultsmentioning
confidence: 90%